2009
DOI: 10.1590/s2236-89062009000200011
|View full text |Cite
|
Sign up to set email alerts
|

Cystoderma, Cystodermella and Ripartitella in Atlantic Forest, São Paulo State, Brazil

Abstract: -(Cystoderma, Cystodermella and Ripartitella in Atlantic Forest, São Paulo State, Brazil). This paper reports on the genera Cystoderma, Cystodermella and Ripartitella from Atlantic Rainforest, Southeast Brazil. They are represented by Cystoderma chocoanum, Cystodermella contusifolia, C. sipariana and Ripartitella brasiliensis. Cystoderma chocoanum is reported for the fi rst time outside the type locality (Colombia) and its relationship with others species of Cystoderma, based on nLSU rDNA sequences, is discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Lepiota cristata (Bolton) P. Kumm. (1871: 137), strain HKAS 61649, was used as the outgroup for the combined ITS-LSU dataset, following Capelari & Asai (2009).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Lepiota cristata (Bolton) P. Kumm. (1871: 137), strain HKAS 61649, was used as the outgroup for the combined ITS-LSU dataset, following Capelari & Asai (2009).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…However, DNA-based phylogenetic studies showed that R. ponderosa belonged to Cercopemyces T.J. Baroni, Kropp & V.S. Evenson (2014: 786), whereas R. sipariana has been transferred into Cystodermella Harmaja (2002: 43) (Capelari & Asai 2009, Zhang et al 2019. Ripartitella rickenii was also transferred to Cercopemyces (Dima & Nagy 2015), without much comment, however.…”
Section: Introductionmentioning
confidence: 99%
“…This genus was segregated from Cystoderma Fayod not only on the basis of morphology and colour reaction (inamyloid basidiospores) but molecular findings also supported phenotypic differences (variation of ITS and LSU markers) [4,5]. Harmaja [2] described this new genus on the basis of morphoanatomical characters and later many researchers used molecular data to determine the relationship of these two genera [6]. After Moncalvo et al [5], Saar et al [3] described Cystoderma and Cystodermella as distinct monophyletic genera on the basis of LSS and ITS barcodes.…”
Section: Introductionmentioning
confidence: 99%